The Conceptual Complexity of Vocabulary in Elementary‐Grades Core Science Program Textbooks. Issue 4 (25th March 2017) - Fitzgerald, W. Jill; Elmore, Jeff; Kung, Melody; Stenner, A. Jackson
Abstract: The researchers explored the conceptual complexity of vocabulary in contemporary elementary‐grades core science program textbooks to address two research questions: (1) Can a progression of concepts' complexity level be described across grades? (2) Was there gradual developmental growth of the most complex concepts' networks of associated concepts from the beginning of a program to the end? That is, for the most complex concepts, did associated concepts begin to appear in the early grades, with gradual cumulative addition of associated concepts throughout the elementary grades? Gradual accumulation of associated concepts could enable students to progressively construct a mental network of concepts within which a more complex concept could be situated, a network that could facilitate learning of most complex concepts. Two best‐selling, contemporary elementary‐grades core science programs constituted the data source. The researchers employed two measures: a conceptual complexity measure and the number of associated concepts (called nodes in concept networks) for each of the most complex concepts. The researchers conducted multilevel modeling and found that, on the whole, the programs exposed students to increasingly complex concepts with the rise of grades. Few highly complex concepts appeared in the earliest grades. Similarly, few associated concepts for the most complex concepts appeared in the earliest grades. Instead, associated concepts tended to be introduced simultaneously with the most complex concepts in the later grades. That is, on the whole, the programs did not expose students to the opportunity to construct strong affiliated concept networks (clusters of associated constructs) prior to introduction of the most complex concepts.